THE QUR’ANIC PERSPECTIVE: THE URGENCY OF ARABIC LEARNING TO UNDERSTANDING THE QUR’AN - Moh Aman; Husnul Amin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Understanding the Qur’an requires the ability to master Arabic, because this holy book was revealed in that language. Arabic has linguistic structures and uniqueness that influence the meaning of the Qur'an texts. This research aims to explore the urgency of learning Arabic in an effort to deepen understanding of the Qur'an. The research method used is literature review and content analysis from various primary and secondary sources related to the urgency of learning Arabic in understanding the Qur'an. The results of this research show that Arabic is not only a medium for conveying revelation, but also as a key to accessing the deep meanings contained in the Qur'an. Many words in the Qur'an have double meanings and special connotations that can only be understood with in-depth mastery of the Arabic language. In addition, the unique structure of the Arabic language has a big influence on understanding meaning and interpretation. Learning Arabic and the use of technology in learning Arabic makes an important contribution in increasing understanding of the texts of the Qur’an more accurately and in depth. Thus, mastery of Arabic is the main prerequisite for understanding the Qur’an correctly, and strengthening the application of its teachings in everyday life.